Renaissance Utopias: A reading from architecture and urbanism - Martuccelli Casanova, Elio (2020)
This article proposes a review of the Renaissance utopias from their urban approaches and their architectural proposals based on a specific analysis. Although the utopias pretend not to take place, that is, they lack precise location, spaces and architectural forms are revealed by the authors and their respective books. In the first part we will underline the link that exists between the encounter Europe and America with the future production of utopias. In the second part, we will present the profile of four great Renaissance authors (Moro, Campanella, de Andreae and Bacon) with a commentary on their explicitly utopian literary works. Here we propose a critical vision of utopias based on their main urban and architectural characteristics, where we try to show how meanings, limits or contradictions are revealed in each of them in relation to the treatment of space.